Efficiency of treatment of chemoresistant tuberculosis from patients suffering from HIV in Zaporizhzhia region within 2013–2017 - Т. К. Sahaidak; N. О. Skorokhodova; О. І. Akhtyrskyi (Сучасні медичні технології)
Purpose of the study. Is to study the efficiency of treatment of tuberculosis from patients suffering from chemoresistant tuberculosis associated with HIV under the conditions of Zaporizhzhia region during 2013–2017.